Tinjauan Syirik dalam Perspektif Ibnu Qoyyim Al-Jauziyah Tentang Akulturasi Budaya Lokal Terhadap Ajaran Islam - Husen Alfaruq; Roni Ali Rahman (Jurnal Multidisiplin Ibrahimy, 2025)
This research aims to criticize the forms of syirikk in the traditions of Indonesian society due to the acculturation of local culture with Islamic teachings, using the framework of Ibn Qoyyim Al-Jauziyah's thought. The main essence discussed in this research is the strengthening of tawhid as a fundamental principle in Islam, as well as how mistakes in cultural adaptation can lead to shirk practices that are not realized by the community. This research uses a descriptive qualitative method by analyzing various local traditions that contain elements of syirikk even though they have adapted to Islamic teachings. The results show that although the tradition is carried out with the aim of glorifying Allah and maintaining social solidarity, the practice of giving offerings or prayers through intermediaries shows the potential for Syirik that obscures the understanding of the purity of Tawhid. This research highlights the importance of strengthening Tawhid and instilling awareness of the potential for shirk in worship practices and local culture. This research is expected to contribute to understanding syirik that occurs without realizing it and encourage Muslims to be more careful in carrying out religious practices and preserving traditions in order to maintain the purity of Tauhid.